Actualization of Islamic Religious Education (PAI) in Schools - Nadya Syahidah Wafiqah; Maspuroh Maspuroh; Yaya Mulyadi; Alpin Alpin; Siti Hopipah (Al-Alim: Jurnal Pendidikan Agama Islam, 2026)
Islamic Religious Education (PAI) plays a strategic role in shaping the character, morals, and spirituality of students in schools. Actualizing PAI involves more than just delivering material in the classroom, but also implementing Islamic values in real life within the school environment. This article discusses how the actualization of PAI can be realized through curriculum, learning methods, teacher role models, and school culture. It also discusses challenges faced, such as globalization, digital technology, and the diversity of student backgrounds. The study shows that PAI, when implemented holistically, can produce a generation that is not only intellectually intelligent but also possesses spiritual, social, and moral intelligence.